Analisis Implementasi COBIT 4.1 pada STIE Indonesia Banking School serta Dampaknya terhadap Focus IT Governance - Bani Saad (STIE Indonesia Banking School, 2015)
This research aimed to analyze Implementation CobiT 4.1 at STIE Indonesia Banking School and the impact to Focus IT Governance. The deployment questionnaires to respondence were 7 copies. Data assessment using Capability Maturity Model from CobiT 4.1, After assess Capability Maturity Model, the author analyse the impact to IT Governance Focus (5 point).The assessment result shows that maturity level from four domain CobiT 4.1 significantly impact on IT Governance focus at STIE Indonesia Banking School. This domain are IT process at STIE Indonesia Banking School, including Plan & Organise, Acquire & Implement, Deliver & Support, and Monitor & Evaluate. IT Governance Focus: Strategic alignment, Value delivery, Resource Management, Risk Management and Performance Measurement.